2022
DOI: 10.3389/fmed.2022.816045
|View full text |Cite
|
Sign up to set email alerts
|

Specific Metabolites Involved in Antioxidation and Mitochondrial Function Are Correlated With Frailty in Elderly Men

Abstract: BackgroundAs an age-related syndrome, frailty may play a central role in poor health among older adults. Sarcopenia overlaps with the physical domain of frailty, and most existing studies have analyzed the associated factors of frailty and sarcopenia as an isolated state. Perturbations in metabolism may play an important role in the presence of frailty or sarcopenia; however, the metabolites associated with frailty, especially overlapping with sarcopenia remain unclear. In this study, we aimed to explore wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Second, various biomarkers for frailty discovered in metabolomics have chiefly focused on amino acids, 25 while metabolites associated with sarcopenia have not been comprehensively profiled and examined. Meng et al 26 applied a targeted high‐performance liquid chromatography–tandem mass spectrometry approach to distinguish elderly patients with frailty from those without frailty by different characteristic metabotypes and found similar characteristic metabotypes between frailty and F&S patients. With sarcopenia or not does not significantly impact the metabolic characteristics of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Second, various biomarkers for frailty discovered in metabolomics have chiefly focused on amino acids, 25 while metabolites associated with sarcopenia have not been comprehensively profiled and examined. Meng et al 26 applied a targeted high‐performance liquid chromatography–tandem mass spectrometry approach to distinguish elderly patients with frailty from those without frailty by different characteristic metabotypes and found similar characteristic metabotypes between frailty and F&S patients. With sarcopenia or not does not significantly impact the metabolic characteristics of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the serum concentration of these metabolites, the worse the physical function of patients with sarcopenia. 17,97 The toxic effects of fatty acids and their acylcarnitine derivatives mainly depend on the saturation and chain length of fatty acids, and thus, saturated long-chain fatty acids are the most lipotoxic. LCFA comprise all fatty acids with more than 12 carbon atoms in the chain, of which palmitic acid and stearic acid and their acylcarnitine derivatives are the most harmful to muscle function.…”
Section: Medium and Long-chain Fatty Acids And Medium And Long-chain ...mentioning
confidence: 99%
“…Observational studies have shown a significant downward trend in the serum levels of lysophosphatidylcholine (LPC) in patients with sarcopenia, indicating that LPC is one of the characteristic metabolites distinguishing elderly people with and without sarcopenia. 17,97,103 The serum levels of LPCs contributing significantly to this discrimination between elderly people with and without sarcopenia are LPC 16:0, LPC 18:0, and LPC 18:2, which are also the most abundant LPC present in human plasma.…”
Section: Lysophosphatidylcholinementioning
confidence: 99%
“…A study in men with frailty syndrome (asthenia) found that the frailty phenotype was characterized by lower concentrations of isovalerylcarnitine, higher levels of octanoyl-L-carnitine, decanoyl-L-carnitine, dodecanoyl-L-carnitine, and tetradecanoyl-Lcarnitine. Metabolic profiles with measurement of glycine and tryptophan levels can distinguish elderly men with frailty from people without frailty 51 . Similar results on the increased risk of developing frailty syndrome in the event of carnitine metabolism disorders were obtained in another study 50 .…”
Section: Prevention Of Endotheliopathies In Covid-19 Patientsmentioning
confidence: 99%